Hierarchical ZSM-5 Catalysts: The Effect of Different Intracrystalline Pore Dimensions on Catalyst Deactivation Behaviour in the MTO Reaction - Weissenberger, Tobias; Machoke, Albert; Bauer, Juergen; Dotzel, Ralf; Casci, John L.; Hartmann, Martin; Schwieger, Wilhelm (ChemCatChem, 2020)
Abstract: We present the effect of different combinations of intracrystalline pore systems in hierarchical ZSM-5 zeolites on their performance as MTO catalysts. We prepared ZSM-5 zeolites with additional intracrystalline mesoporous, intracrystalline macropores and a novel ZSM-5 type zeolite with intracrystalline meso and macropores. The catalytic results showed that both used catalysts with mesopores and macropores exhibited three times longer catalyst lifetime compared to a conventional catalyst. However, TGA analysis of the deactivated catalysts showed much larger coke content in the mesoporous catalyst than in the macroporous catalyst. Consequently, macropores predominantly led to reduced coke formation rate while additional mesopores predominantly enhanced the resistance against deactivation by coke. Combining both intracrystalline meso and macropores in one catalyst lead to a tenfold increase in catalyst lifetime. Besides the effect on the catalyst lifetime there was also a strong effect of the additional pore systems on the selectivity of the catalysts. The catalysts containing mesopores showed reduced selectivity to short chain olefins and increased selectivity to larger hydrocarbons in comparison to the catalysts without a mesopores system.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Heterogeneous catalysis; hierarchical materials; Mesoporous materials; nanostructures; Zeolites